Selective Proteolysis of α‐Lactalbumin by Endogenous Enzymes of Human Milk at Acidic pH. Issue 18 (16th July 2019) - Gan, Junai; Zheng, Jingyuan; Krishnakumar, Nithya; Goonatilleke, Elisha; Lebrilla, Carlito B.; Barile, Daniela; German, J. Bruce
Abstract : Scope: The use of human milk products is increasing for high‐risk infants. Human milk contains endogenous enzymes that comprise a dynamic proteolytic system, yet biological properties of these enzymes and their activities in response to variations including pH within infants are unclear. Human milk has a neutral pH around 7, while infant gastric pH varies from 2 to 6 depending on individual conditions. This study is designed to determine the specificity of enzyme–substrate interactions in human milk as a function of pH. Methods and results: Endogenous proteolysis is characterized by incubating freshly expressed human milk at physiologically relevant pH ranging from 2 to 7 without the addition of exogenous enzymes. Results show that the effects of pH on endogenous proteolysis in human milk are protein‐specific. Further, specific interactions between cathepsin D and α‐lactalbumin are confirmed. The endogenous enzyme cathepsin D in human milk cleaves α‐lactalbumin as the milk pH shifts from 7 to 3. Conclusions: This study documents that selective proteolysis activated by pH shift is a mechanism for dynamic interactions between human milk and the infant. Controlled proteolysis can guide the use of human milk products based on individual circumstance. Abstract : Human milk contains enzymes, yet their activities in response to variations including pH within infants are unclear. Using peptidomics approaches, this work shows that human milk enzyme cathepsin D cleaves α‐lactalbumin as the pH shifts from 7 to 3. The study shows that selective proteolysis activated by pH shift is a mechanism for dynamic interactions between human milk and the infant.